The Effect of Income and Operating Expenses on Net Profit with Capital EXpenditure as a Moderation Variable (Study on Sector Companies Energy Listed on The Idx Period 2018 - 2021) - Febrinia ANASTHASYA; Jullie J. SONDAKH; Claudia W.M. KOROMPIS (Indonesia Strategic Sustainability, 2022)
This study aims to determine the effect of income and operating expenses on net profit with capital expenditure as a moderation variable in energy sector companies listed on the Indonesia Stock Exchange. The type of research method used is quantitative. The population used in this study are energy sector companies listed on the Indonesia Stock Exchange. The samples used in this study were energy sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period that met the predetermined criteria, namely 41 samples. The data source used in this study is secondary data with documentation data collection techniques. The analytical techniques used in this study include descriptive statistical analysis, outer model, inner model and hypothesis testing with the help of the SmartPLS 3.0 program. The results indicate that income affects net profit, operating expenses do not affect net profit and capital expenditure does not moderate the effect of income and operating expenses on net profit.